2014
DOI: 10.1007/s12149-014-0818-9
|View full text |Cite
|
Sign up to set email alerts
|

Bone uptake of Tc-99m MIBI in patients with hyperparathyroidism

Abstract: Bone uptake of MIBI in patients with HPT is commonly related to a high level of iPTH and ALP; it probably reflects an active stage of MBD, and it should be monitored during the conventional Tc-99m MIBI scintigraphy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Qui et al [ 22 ] have described the detection of vertebral metastases on a MIBI scan, in a patient with a rare parathyroid carcinoma. Zhao and Wang [ 23 ] have highlighted the relation between a high level of intact PTH and bone uptake of MIBI, concluding that this could reflect a stage of metabolic bone disease.…”
Section: Discussionmentioning
confidence: 99%
“…Qui et al [ 22 ] have described the detection of vertebral metastases on a MIBI scan, in a patient with a rare parathyroid carcinoma. Zhao and Wang [ 23 ] have highlighted the relation between a high level of intact PTH and bone uptake of MIBI, concluding that this could reflect a stage of metabolic bone disease.…”
Section: Discussionmentioning
confidence: 99%
“…One false positive lesion found on the 99m Tc-MIBI scintigraphy was the focal 99m Tc-MIBI uptake of the manubrium sterni. Previous study supposed that the 99m Tc-MIBI uptake of bone might reflect the presence of active metabolic bone disease, but did not reflect the changes that occurred in microstructure of bone [40]. However, this remains to be evaluated further.…”
Section: Discussionmentioning
confidence: 87%
“…One false-positive lesion found on dual-phase 99m Tc-MIBI scintigraphy was attributed to the focal 99m Tc-MIBI uptake of the manubrium sterni. A previous study suggested that the 99m Tc-MIBI uptake of bone might reflect the presence of active metabolic bone disease but did not reflect changes that occurred in the microstructure of bone [42]. However, this remains to be evaluated further.…”
Section: Discussionmentioning
confidence: 89%